1981
DOI: 10.1007/bf00391179
|View full text |Cite
|
Sign up to set email alerts
|

The polysaccharide structure of potato cell walls: Chemical fractionation

Abstract: Cell walls of potato tubers were fractionated by successive extraction with various reagents. A slightly degraded pectic fraction with 77% galacturonic acid was extracted in hot, oxalate-citrate buffer at pH 4. A further, major pectic fraction with 38% galacturonic acid was extracted in cold 0.1 M Na2CO3 with little apparent degradation. These two pectic fractions together made up 52% of the cell wall. Most of the oxalate-citrate fraction could alternatively be extracted with cold acetate-N,N',N'-tetracetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(76 citation statements)
references
References 31 publications
4
71
0
1
Order By: Relevance
“…The AG backbone may consist of separate blocks of galactan and arabinan, somewhat analogous to the alternating HG and RG blocks in pectin (but which, unlike those in pectin, contain no uronic acid). Reasons were given previously (4) (32), and cultured rose cell primary walls (12), from the results of analogous extraction procedures. Furthermore, although particular pectin molecules might be cross-linked by ester linkages as noted above, the pea pectin Mr profile clearly shows that its molecules are not interlinked extensively enough to form a network.…”
Section: Size Features Of Hemicellulosesmentioning
confidence: 99%
See 1 more Smart Citation
“…The AG backbone may consist of separate blocks of galactan and arabinan, somewhat analogous to the alternating HG and RG blocks in pectin (but which, unlike those in pectin, contain no uronic acid). Reasons were given previously (4) (32), and cultured rose cell primary walls (12), from the results of analogous extraction procedures. Furthermore, although particular pectin molecules might be cross-linked by ester linkages as noted above, the pea pectin Mr profile clearly shows that its molecules are not interlinked extensively enough to form a network.…”
Section: Size Features Of Hemicellulosesmentioning
confidence: 99%
“…Certain authors (50,69), however, have held that no neutral arabinose or galactose polysaccharides have been isolated from primary walls by a procedure that could not have produced them artifactually by splitting side chains off of RG molecules. Jarvis et al (32) regarded extraction of pectins with oxalate-citrate, pH 4, at 100°C as slightly degradative. Their GFC evidence for this did not eliminate the alternative that this treatment caused some dissociation of large molecular aggregates rather than degradation.…”
Section: Size Features Of Hemicellulosesmentioning
confidence: 99%
“…Exhaustive extraction for 24 h with 25% sodium hydroxide containing 5% sodium borate and 1% sodium borohydride (5) was attempted over the latter residue (EK). The extracts and the new residue (EN) were treated as above, and similar insoluble products were obtained: PDN (which precipitated during the dialysis), PCN (which precipitated during concentration), and PN (which precipitated between 40-50% ethanol concentration); 85% ethanol-soluble products were recovered as usual (SN).…”
Section: Extractionmentioning
confidence: 99%
“…1 ,2) However, Jarvis et al: reported that there were two rhamnogalacturonan-based fractions in the potato cell wall. 3,4) The first fraction, extractable with a hot chelating solvent, was probably associated with other polysaccharides only through calcium-complexing and the steric effect of its own molecular size. The second fraction, extracted subsequently with mild alkali, was retained by covalent bonding.…”
mentioning
confidence: 99%
“…These two fractions showed a close similarity in the mode of linkages of sugar residues, although the latter was rich in galactan and arabinan side chains. 4 ) In the previous paper, we reported the structure of pectin isolated from tobacco midrib by extraction with EDTA.5) The pectin had a rhamnogalacturonan backbone to which side chains of galactan and arabinan were linked probably to C-4 of the L-rhamnosyl residues.…”
mentioning
confidence: 99%